PENGARUH MOBILISASI DINI TERHADAP KENYAMANAN FISIK PADA PASIEN POST OPERASI PLATING FEMUR DI RUANG BOEGENVILE RS TK. II DR. SOEPRAOEN MALANG - Rahmania Ambarika; Novita Ana Anggraini; Lingga Kusuma Wardani (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2021)
The community of postoperative femur fracture patients are often afraid to move because of pain or fear that the bones cannot be properly connected so that they limit activities that result in swelling in the operation area. Postoperative femur plating patients in the room often experience edema because after surgery they just lie down without muscle training therapy and reduce physical comfort in postoperative patients. The purpose of this study is the difference before and after early mobilization. This study used a pre-experimental research design one group pre post test design. The population was femoral pot op plating patients in Bougenvile Hospital. TK.II Dr. Soepraoen Malang with a sample of 30 respondents. The sampling technique used was accidental sampling. Collecting data using questionnaires and observations and analyzed using Wilcoxon statistical test. The results showed that most of the respondents before giving the mobilization experienced sufficient discomfort 17 (56.7%), almost all respondents after giving the mobilization experienced moderate discomfort as many as 21 (70%). From the results of the statistical test p value 0,000 means that Ho is rejected, so the conclusion is that there is an effect of mobilization on physical comfort in post op plating femure patients in the Boegenvile Room, RS.TK.II Dr. Soepraoen Malang. Mobilization improves air circulation and improves blood circulation in the post op area thereby increasing comfort